Novel efficient methods for measuring mesophyll anatomical characteristics from fresh thick sections using stereology and confocal microscopy: application on acid rain-treated Norway spruce needles - Albrechtová, Jana; Janácek, Jirí; Lhotáková, Zuzana; Radochová, Barbora; Kubínová, Lucie (Journal of experimental botany, 2007)
Recent design-based stereological methods that can be applied to thick sections cut in an arbitrary direction are presented and their implementation for measuring mesophyll anatomical characteristics is introduced. These methods use software-randomized virtual 3D probes, such as disector and fakir test probes, in stacks of optical sections acquired using confocal microscopy. They enable unbiased estimations of the mean mesophyll cell volume, mesophyll cell number in a needle, and for the first time an internal surface area of needles or other narrow leaves directly from the fresh tissue cross-sections cut using a hand microtome. Therefore, reliable results can be obtained much faster than when using a standard microtechnical preparation. The proposed methods were tested on Norway spruce needles affected for 1 year by acid rain treatment. The effect of acid rain resulted in changes of mesophyll parameters: the ratio of intercellular spaces per mesophyll cell volume increased, while needle internal surface area, total number of mesophyll cells, and number of mesophyll cells per unit volume of a needle decreased in the treated needles.
Keywords: Carbon Dioxide; Plant Leaves; déšť; oxid uhličitý; světlo; Microscopy, Confocal; smrk; Rain; Photosynthesis; Picea; Light; listy rostlin; konfokální mikroskopie; fotosyntéza